The Importance of Being Trustworthy - Sellman, Derek (2006)
The idea that nurses should be trustworthy seems to be accepted as generally unproblematic. However, being trustworthy as a nurse is complicated because of the diverse range of expectations from patients, relatives, colleagues, managers, peers, professional bodies and the institutions within which nursing takes place. Nurses are often faced with competing demands and an action perceived by some as trustworthy can be seen by others as untrustworthy. In this article some of the reasons for the importance of being trustworthy are offered together with a preliminary discussion about how being a trustworthy nurse is far from straightforward.
Keywords: Virtue; Trustworthiness; professional trust; patient-nurse relationships